2021
DOI: 10.1155/2021/8842267
|View full text |Cite
|
Sign up to set email alerts
|

Infection Prevalence and Antibiotic Resistance Levels in Ureaplasma urealyticum and Mycoplasma hominis in Gynecological Outpatients of a Tertiary Hospital in China from 2015 to 2018

Abstract: The aim of this study was to estimate the Ureaplasma urealyticum and Mycoplasma hominis infection prevalence and antibiotic resistance levels in gynecological outpatients. Clinical characteristics and laboratory data of gynecological outpatients of the Fourth People’s Hospital of Chongqing from 2015 to 2018 were retrospectively analyzed. Antibiotic resistance levels in U. urealyticum and M. hominis were defined by a commercial Mycoplasma kit for antibiotic susceptibility testing. Univariate analysis and multiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
2
7
1
Order By: Relevance
“…Due to the low CNS penetration, macrolides are not a valid treatment option for UU meningitis. Although levofloxacin can penetrate the blood-brain barrier [12], several studies have reported that UU has high resistance rates to levofloxacin in China [13,14], and in our case the drug did not significantly relieve the patient's symptoms. However, we still considered levofloxacin to have some effect on UU, and we continued to administer the medication after UU DNA in the CSF was confirmed by NGS.…”
Section: Discussioncontrasting
confidence: 63%
“…Due to the low CNS penetration, macrolides are not a valid treatment option for UU meningitis. Although levofloxacin can penetrate the blood-brain barrier [12], several studies have reported that UU has high resistance rates to levofloxacin in China [13,14], and in our case the drug did not significantly relieve the patient's symptoms. However, we still considered levofloxacin to have some effect on UU, and we continued to administer the medication after UU DNA in the CSF was confirmed by NGS.…”
Section: Discussioncontrasting
confidence: 63%
“…In a study in Beijing, the resistance rates of M. hominis to CIP, LEV, and SPA were 82.2%, 62.2%, and 80.0%, respectively, and few strains showed resistance to MIN, DOX, and JOS [ 35 ]. These results were similar to those of some other studies in China [ 37 39 ] and current research. As a result, the antibiotic sensitivity profile of M. hominis isolated in various regions of the genitourinary tract can be utilized as a reference for the treatment of M. hominis BSI.…”
Section: Discussionsupporting
confidence: 94%
“…In addition to the most prevalent GV infection rates, the other three common pathogens that were found to infect Vietnamese women's vagina causing single or multiple infections, included CA, CT, and MH, with 55.14%, 12.34%, and 10.28%, respectively. These three rates were relatively close to those of previous studies regarding the 64% CA infection rate found in Nigerian women [33], 8.8% CT infection rate found in Chilean adolescents [34], and approximately 11% of MH infection rates found in Brazilian women without gynecologic complaints and at reproductive age [35] and in gynecological outpatients of a tertiary hospital in China from 2015 to 2018 [36]. The rate of MH in our study was lower than that of 17.34% in Tanzanian women [37] but higher than that of 3.39% in infertile women in Romania's Northeast Region [38].…”
Section: Plos Onesupporting
confidence: 88%
“…To date, there have been a number of reports of patients co-infected with 2-3 STIs pathogens [32,34,36,[38][39][40][41][42]. However, to the best of our knowledge, there have been no publications showing patients co-infected with 4-5 pathogens.…”
Section: Plos Onementioning
confidence: 99%